Insights on natural products and their derivatives in tuberculosis management - Goyal Rajat; Susheel Kumar; Garg Kajal; Neha Rani; Chopra Hitesh; Wilson Kashish; Gupta Sumeet (Scripta Medica)
Tuberculosis (TB), a bacterial disease primarily affecting middleas well as low-income countries, poses a significant public health threat. Natural products have historically been and remain a vital source of fresh medications for treating various diseases. The renewed interest in natural product research is partly a result of the increasing prevalence of drug-resistant Mycobacterium tuberculosis (MTb) strains along with adverse outcomes associated with firstand second-line anti-tubercular drugs. The TB complexity and the complications arising from the use of allopathic medications, such as multidrug resistance, highlight the effectiveness of natural medications in this context. Therefore, it is crucial to explore new treatment therapies to effectively mitigate the harmful effects associated with TB. More research is needed on various natural substances, both independently and in combination with currently approved drug regimens, as potential TB treatment options.